An Analysis of Security System for Intrusion in Smartphone Environment - Maya Louk; Hyotaek Lim; HoonJae Lee (The Scientific World Journal)
There are many malware applications in Smartphone. Smartphone’s users may become unaware if their data has been recorded and stolen by intruders via malware. Smartphone—whether for business or personal use—may not be protected from malwares. Thus, monitoring, detecting, tracking, and notification (MDTN) have become the main purpose of the writing of this paper. MDTN is meant to enable Smartphone to prevent and reduce the number of cybercrimes. The methods are shown to be effective in protecting Smartphone and isolating malware and sending warning in the form of notification to the user about the danger in progress. In particular, (a) MDTN process is possible and will be enabled for Smartphone environment. (b) The methods are shown to be an advanced security for private sensitive data of the Smartphone user.